2019
DOI: 10.1074/jbc.ra119.010518
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human trophoblast syncytialization by histone demethylase LSD1

Abstract: A successful pregnancy is critically dependent upon proper placental development and function. During human placentation, villous cytotrophoblast (CTB) progenitors differentiate to form syncytiotrophoblasts (SynTBs), which provide the exchange surface between the mother and fetus and secrete hormones to ensure proper progression of pregnancy. However, epigenetic mechanisms that regulate SynTB differentiation from CTB progenitors are incompletely understood. Here, we show that lysine-specific demethylase 1 (LSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 92 publications
0
13
0
Order By: Relevance
“…The pattern of placental methylation is crucial for the regulation of genes involved in trophoblast invasion and placental development, which are key events for fetal growth [ 11 , 12 ]. For example, the expression of the gene encoding chorionic gonadotropin is related to the gestational week of pregnancy and its expression is epigenetically regulated [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pattern of placental methylation is crucial for the regulation of genes involved in trophoblast invasion and placental development, which are key events for fetal growth [ 11 , 12 ]. For example, the expression of the gene encoding chorionic gonadotropin is related to the gestational week of pregnancy and its expression is epigenetically regulated [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we hypothesize that TPR-targeted LSD1 might de-methylate TFs, such as MEF2D or MYOD1, at the Myh4 and Olfr376 promoters, as described by [ 24 ]. Another possibility is that LSD1 targets TFs to the TPR-associated genes, as shown for TF GATA2, which promotes RNA polymerase II recruitment and activates the transcription of genes crucial for the fusion of trophoblast cells into syncytiotrophoblasts [ 57 ]. Alternatively, the deregulation of Myh4 and Olfr376 in TPR-depleted cells could occur independently of LSD1, for instance through gene organization changes within the cell nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…The knockout embryos also displayed morphological abnormalities such as smaller sizes and reduced trophoblast development compared to wildtype mice. In addition, a recent study using human choriocarcinoma (BeWo) cells revealed a role for KDM1A in cytotrophoblast differentiation into syncytiotrophoblasts by recruiting transcription factor GATA2 and stimulation of hCG production ( Milano-Foster et al., 2019 ).…”
Section: Kdm1a and Gene Regulation In Trophoblast Cells Placental Devmentioning
confidence: 99%